Population aging and changes in the age structure of Slovakia - Bucher, Slavomír (Journal for Geography, 2012)
The age group structure of the population in the districts of Slovakia was highlighted by means of an analysis of the three big age groups: 0 – 19 years, 20 – 64 years and 65 years and older. The paper reports on the development of the characteristics of the burden carried by the productive population in consequence of the demographic ageing of population in the conditions of the Slovakian regions. The main task of the paper was the identification the tendencies in age structure of Slovak population. Statistical methods and mathematics proceeding are used to compare different parameters age structure (e. g. index of ageing, youth dependency ratio etc.). That can be the ageing process as well as the forming of the population age structure considered as a demographical phenomenon with a fairly high degree of complexity. The results of the study will enhance the knowledge about demographic characteristics of Slovakia and therefore might be useful for further research in the field.
Keywords: age structure; Slovakia; pre-productive population rate; population ageing